Exploring Several Social Traditions In Persian literature (Until The 8th Hegira Century) - Ranjbar Makki, Reza (2020)
Undoubtedly, the social customs and traditions and beliefs are enumerated amongst parts of Persian culture and literature. The architects of Persian literature’s palace have taken advantage of these customs as themes and motifs for their poems and proses. These works are the full-scale mirror of their contemporary society. Certain beliefs, traditions and customs have been prevalent in certain periods. The poets or the authors have been fostered and developed in these pervasive beliefs and traditions in their periphery; they have seen them and lived with them and, willingly or unwillingly, used them in their literary works. Such types of matter have been understandable at the time of the poet by the elites and general public and everybody could readily discern them; but, these materials have been erased of the people’s minds in the course of time and for various reasons and they have sounded and looked rather odd to the later generations.The present study intends to investigate, within the research’s tolerance, the social traditions and customs reflected in the Persian prose and poetry works till 8th hegira century as topics less frequently dealt with so that the individuals interested in Persian language can be made familiar with the minutes of their thoughts and arts as well as with the national and cultural identity thereby to be assisted in resolving the difficulties and reaching a more precise understanding of the prose and poetry works.